2012
DOI: 10.1016/j.conbuildmat.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical evolution of Portland cement blended with silica nanoparticles and its effect on mechanical strength

Abstract: Mineralogical analysis done on Spanish Portland cement Type I pastes, blended with nanosilica was carried out by conventional and high-resolution thermogravimetric analysis (TG-HRTG) and X-ray diffraction (XRD) in order to determine the quantity of the different mineralogical phases obtained during the hydration process. Simultaneously, mortars with the same materials and replacement ratio were made in order to assess their compressive strength for up to 28 days of curing time. In this paper, the rate and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 22 publications
(12 reference statements)
4
38
0
5
Order By: Relevance
“…For 28 days, the hydration process for cement pastes obtained for both mixing methods is similar. Water loss that takes part in the CSH gel (T1) at 28 days for cement pastes with NS is higher than that for the MS ones, with this indicating that nanosilica produces a higher quantity of hydrated phase and showing agreement with the literature (Tobón et al [59]). …”
Section: Figures 4(a)-4(c) Andsupporting
confidence: 80%
“…For 28 days, the hydration process for cement pastes obtained for both mixing methods is similar. Water loss that takes part in the CSH gel (T1) at 28 days for cement pastes with NS is higher than that for the MS ones, with this indicating that nanosilica produces a higher quantity of hydrated phase and showing agreement with the literature (Tobón et al [59]). …”
Section: Figures 4(a)-4(c) Andsupporting
confidence: 80%
“…For example, nanotechnology has been implemented in the study of building materials in order to improve the mechanical properties and give the materials other additional properties. In these studies, the addition of carbon nanotubes to reduce fissures and improve mechanical properties [1], as well as the insertion of nanoparticles of silica (n-SiO2) [2] and iron oxide (Fe2O3) for the sealing of nanopores [3] has been highlighted. Other types of features have been given to cement, when broadband semiconductor nanoparticles are added, such as the decontaminating of air, and the self-cleaning in buildings, through photocatalytic activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of HRTG have commonly been applied in the decomposition of minerals (hydrotalcite, organoclays, peisleyite, montmorillonite), polymers and oil shales [6][7][8][9][10][11][12][13]. In the field of civil construction, only few studies have been reported using HRTG technique [14][15][16][17][18]. Payá et al [14] applied this technique in the study of dehydration of gypsum, yielding the total separation of the two decomposition processes for CaSO 4 .2H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Payá et al [14] applied this technique in the study of dehydration of gypsum, yielding the total separation of the two decomposition processes for CaSO 4 .2H 2 O. The use of HRTG was performed by Tobón et al [18] in order to assess the effect of SiO 2 nanoparticles blended in Portland cement pastes in the range 100-300 ºC, related to the dehydration of calcium silicate hydrate (C-S-H gel), C-A-S-H and C-A-H. For HRTG, the hydrated phases were successfully separated in the DTG curve.…”
Section: Introductionmentioning
confidence: 99%